Implementasi Kepemimpinan Institut Agama Islam Negeri (IAIN) Jember ‎Dalam Meningkatkan Mutu Kelembagaan Melalui Ma’had Al-Jami’ah - Nuruddin; Zainul Hakim (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2023)
The success of institutions in improving institutional quality is a major effort for leaders in carrying out their rle as leaders who, with their managerial capabilities, seek to acheve institutional quality improvement. The focus of this research is the implementation of institutre leadership in improving the institutional quality of the Jember State Islamic Institute (IAIN) through Ma’had Al-ami’ah. This research uses a qualitative approach with a case study design. Data collection techniques are carried out by: interviews, observations, and documentation studies. The results of the research include Ma’had Al-Jami’ah IAIN Jember. Which is one of the institutional units of IAIN Jember, which already has an organizational structure, students, learing curriculum, infrastructure, and finance. Second, the chancellor together with the leaders of the institure implement their leadership in improving instituonal quality. Third, the implementation of institutional quality improvement is reflected in the design of the Ma’had Al-Jamiah curriculum and strives to meet infrastructure needs.